Detection of enterotoxins genes in coagulase-negative staphylococci isolated from foods - Cunha, Maria de Lourdes Ribeiro de Souza da; Peresi, Eliana; Calsolari, Regina Adriana Oliveira; Araujo, Joao Pessoa (Springer, 2006)
Staphylococcal food poisoning is caused by ingestion of enterotoxins preformed in the food contaminated essentially through human manipulation or raw material obtained from animals. Although coagulase-positive Staphylococcus aureus is the main agent responsible for food intoxication, some researches emphasise that coagulase-negative staphylococci (CNS) are able to produce staphylococcal enterotoxins and may be a potential cause of food poisoning. In the present study CNS were isolated from foods and the toxigenic capacity of the strains determined. A total of 88 food samples were analysed and 22.7% were positive for CNS strains. Staphylococcal counts ranged from 3.0 x 10(2) to 1.4 x 10(6) CFU/g or mL of food examined. S. epidermidis predominated among the isolates (40%). Further isolates included S. xylosus (20%), S. warneri (20%), S. saccharolyticus (15%), and S. hominis (5%). Four isolates were positive for enterotoxin genes, as detected by polymerase chain reaction, with sea being the predominant gene. Although no enterotoxin production was detected by the reverse passive latex agglutination method, the data showed that the toxigenic capacity of CNS should not be ignored, requiring investigation of this group of microorganisms in food.
Keywords: coagulase-negative staphylococci; PCR; enterotoxins